Case report: Paralysis after epidural analgesia due to a hemorrhage of pure epidural venous hemangioma - Li, Jiahui; Xie, Pengyun; Liu, Xiaolei; Li, Daheng; Tang, Jing (Frontiers in Neurology, 2023)
Abstract (< 250 words) Purpose: To report on a case of sudden paralysis after epidural analgesia to raise awareness of the condition and the importance of early identification and appropriate treatment of extradural venous angiomas. Clinical Features: A 28 year old male with myofascial pain syndrome experienced paraplegia after receiving an epidural block as pain relief, which was later discovered to be caused by hemorrhage from extradural venous angiomas. Decompression surgery was performed immediately and successfully. A follow-up examination was performed 5 months after surgery. The patient reported improvement in the retention of urine. The muscle strength in both his lower extremities had recovered to 4/5 but exhibited considerable residual spasticity. Conclusions: To relieve undefined pain, careful balancing of the benefits and risks to patient health to reduce the risk of complications before epidural analgesia.